2020
DOI: 10.1002/jcp.29816
|View full text |Cite
|
Sign up to set email alerts
|

The effects of macrophage‐mediated inflammatory response to the donor site on long‐term retention of a fat graft in the recipient site in a mice model

Abstract: Inflammatory responses mediated by macrophages play a role in tissue repair. However, it is unclear whether the repair in the donor site after liposuction would have any effects on fat graft retention in the recipient site. This study is designed to evaluate the effects of a macrophage‐mediated inflammatory response in donor sites on long‐term retention of fat grafting. In this study, mice were randomly divided into two groups. One underwent simulated liposuction, called the fat procurement plus grafting (Pro‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…It may be related to the different mice models used to construct the wound models. The recipient cells could migrate to the damaged site [30,31]. In our study, mice bone marrow is damage.…”
Section: Discussionmentioning
confidence: 69%
“…It may be related to the different mice models used to construct the wound models. The recipient cells could migrate to the damaged site [30,31]. In our study, mice bone marrow is damage.…”
Section: Discussionmentioning
confidence: 69%
“…5.1 During the early stage after autologous fat grafting, circulating inflammatory cells, especially macrophages, will preferentially infiltrate the donor site. In this stage, the level of inflammation will be lower at the recipient than at the donor site, resulting in delayed repair of the recipient area, which may hinder the reconstruction of the ECM during the early stage ( Wang et al, 2020 ). Thus, early supplementation of the recipient area with an adequate number of macrophages may increase the graft retention rate by improving angiogenesis and ECM remodeling ( Phipps et al, 2015 ).…”
Section: Clinical Avoidance Of Poor Extracellular Matrix Remodeling After Graftingmentioning
confidence: 99%
“…Excessive macrophage infiltration can also result in the excess secretion of type VI collagen and result in fibrosis ( Schnoor et al, 2008 ; Spencer et al, 2010 ). The rapid and massive infiltration and rapid evacuation of macrophages after fat grafting may lead to better tissue vascularization and facilitate ECM remodeling ( Anghelina et al, 2006 ; Wang et al, 2020 ). Therefore, trying to deplete the macrophages from transferred fat during the late stage may reduce the excessive deposition of ECM and reduce fibrosis ( Cai et al, 2017 ).…”
Section: Clinical Avoidance Of Poor Extracellular Matrix Remodeling After Graftingmentioning
confidence: 99%
“…By the way, Wang et al 24 proposed an interesting point: Due to the important role of macrophages in tissue regeneration, both the donor site and recipient site need to recruit macrophages after autologous fat grafting, but the number of macrophages in a certain time is limited, so would the repair of donor site have some impacts on fat survival in the recipient site? To verify the question, they designed a study and the results indicated that there was indeed a competition between the two sites.…”
Section: Potential Use Of Macrophage Therapy and Concernsmentioning
confidence: 99%